2019
DOI: 10.1038/s41598-019-45979-2
|View full text |Cite
|
Sign up to set email alerts
|

Uridine as a protector against hypoxia-induced lung injury

Abstract: The effect of the activation of the mitochondrial ATP-dependent potassium channel (mitoK ATP ) on the ultrastructure of rat lung in acute hypoxic hypoxia (7% of oxygen in nitrogen, exposure 30 min) was studied. It was shown that uridine, a precursor of the mitoK ATP activator UDP, exerted a protective effect against hypoxic damage to the lung. The administration of uridine to animals prior to hypoxia decreased the number of mitochondria with altered ultrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Currently available data indicate that the activation of mitoK ATP is able to prevent the development of oxidative stress in the myocardium, the decomposition of ATP and creatine phosphate, reduces the generation of ROS and blocks the oxidation of glutathione [7,8]. Moreover, it was shown, including our data, that mitoK ATP is involved in the adaptation of animals to hypoxia, exerting a positive effect not only in the myocardium, but also in the lungs [12,13], which is of particular importance in P, which is accompanied by the formation of a hypoxic state in the organism, at least of the respiratory type [14].…”
Section: Introductionsupporting
confidence: 66%
“…Currently available data indicate that the activation of mitoK ATP is able to prevent the development of oxidative stress in the myocardium, the decomposition of ATP and creatine phosphate, reduces the generation of ROS and blocks the oxidation of glutathione [7,8]. Moreover, it was shown, including our data, that mitoK ATP is involved in the adaptation of animals to hypoxia, exerting a positive effect not only in the myocardium, but also in the lungs [12,13], which is of particular importance in P, which is accompanied by the formation of a hypoxic state in the organism, at least of the respiratory type [14].…”
Section: Introductionsupporting
confidence: 66%
“…In agreement with this hypothesis, it has been recently reported that the CDA-dependent deoxyuridine salvage may function as anti-oxidant to protect pancreatic cancer cells against ROS [ 54 ]. Specifically, it has been suggested that uridine has an activating effect on the mitochondrial ATP-dependent potassium channel (mitoKATP) thereby reducing H 2 O 2 levels in the mitochondria and thus the development of oxidative stress [ 55 ]. Indeed, it has been shown that CDA-dependent deoxyuridine can relieve ROS-induced endoplasmic reticulum stress to promote cancer cell survival [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of action of H 2 S on KATP-channels remains unclear, but it is suggested that hydrogen sulfide exerts its influence through the K+ conductivity feature, and specific KATP-channel inhibitors completely inhibit H 2 S effects on it [1]. We are inclined to take this view, since it is precisely such dynamics of changes of the mitochondrial apparatus in different tissues of the body that promotes not only the ultrastructure but also the function of the mitochondria [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…Another of our findings is the activation of autophagy in hypertension. As autophagy is thought to be a process that contributes not only to the death of damaged cells but also to their preservation (by preventing apoptosis by mitochondrial pathways) [4,19], it can be assumed that in hypertension regardless of patients' age, such a mechanism is activated at least in blood cells. Addition to the traditional therapy of AH donor H 2 S did not lead to significant changes in the intensity of mitochondrial autophagy, although in the literature there are isolated data on the reduction of the process under the influence of endogenous H 2 S [15,22].…”
Section: Discussionmentioning
confidence: 99%